A REVISION OF LANGOBARDISAURUS ROSSII BIZZARINI AND MUSCIO, 1995 FROM THE LATE TRIASSIC OF FRIULI (ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2007)
A nearly complete but poorly preserved amniote from the Middle-Upper Norian of Friuli (NE Italy), previously attributed to a new species of the protorosaur genus Langobardisaurus (L. rossii Bizzarini & Muscio, 1995), is re-described. Study reveals that the specimen does not exhibit any protorosaurian characters, instead all available evidence supports its attribution to the Lepidosauromorpha. Some skull characters might support sphenodontian affinities, but preservation is too poor to allow a firm assigment to this group.